Hubungan Identifikasi Risiko Dekubitus Skala Braden dengan Penerapan Range of Motion pada Pasien Stroke - Hadrianti, Dessy; Olviani, Yurida; Saherna, Jenny; M. Hidayatullah, M. Hidayatullah (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Stroke is usually characterized by paralysis of the limbs on one side of the body, which causes the sufferer to experience pressure ulcers. One of the treatments that can be done for stroke sufferers is Range of Motion which helps restore the condition of stroke sufferers who experience paralysis, so that there is no risk of pressure ulcers. Objective: to determine the relationship between range of motion management and prevention of pressure ulcers in stroke patients at H. Damanhuri Barabai Regional Hospital in 2023. Method: quantitative correlational with cross sectional research design. The population was all stroke patients who were admitted to class 1, 2 and 3 at H. Damanhuri Barabai Regional Hospital. The sampling technique was Consecutive sampling of 96 respondents. The instrument consists of the operational standard Range of Motion (ROM) and the risk of pressure ulcers using the Branden scale. Results: The majority of stroke patients were 46-55 years old, 57 respondents (59.4%), 49 respondents (51%) had a high school education and 28 respondents (29.2%) worked in the private sector. The majority of risk prevention of pressure ulcers in stroke patients was moderate, amounting to 38 respondents (39.6%). The majority of respondents' understanding of the management of range of motion in stroke patients was not carried out by 51 respondents (53.1%). There is a relationship between managing range of motion and preventing the risk of pressure ulcers in stroke patients at H. Damanhuri Barabai Regional Hospital in 2023 Keywords : Identification, Prevention of the Risk Pressure Ulcers, Braden Scale, Range of Motion, Stroke  ABSTRAK Edukasi Stroke biasanya ditandai dengan kelumpuhan anggota gerak di salah satu sisi anggota tubuh, yang menyebabkan penderita mengalami luka dekubitus. penatalaksanaan yang bisa dilakukan pada penderita stroke salah satunya yaitu Range of motion yang membantu memulihkan keadaan penderita stroke yang mengalami kelumpuhan, agar tidak terjadinya risiko dekubitus. Tujuan: mengetahui hubungan penatalaksaaan Range of motion dengan pencegahan resiko dekubitus pada pasien stroke di RSUD H. Damanhuri Barabai tahun 2023. Metode: kuantitatif korelasional dengan desain penelitian cross sectional. Populasi adalah seluruh pasien pederita stroke yang dirawat inap kelas 1, 2 dan 3 RSUD H. Damanhuri Barabai. Teknik sampling Consecutive sampling sebanyak 96 responden. Instrumen terdiri dari standar operasional Range Of Motion (ROM) dan resiko luka tekan menggunakan skala branden. Hasil: Pasien stroke mayoritas pasien stroke berumur 46-55 tahun sebesar 57 responden (59,4%), berpendidikan SMA sebesar 49 responden (51%) dan pekerjaan swasta sebesar 28 responden (29,2%). Pencegahan resiko dekubitus pada pasien stroke mayoritas sedang sebesar 38 responden (39,6%). Pemahaman responden terhadap penatalaksanaan Range of motion pada pasien stroke mayoritas tidak dilakukan sebesar 51 responden (53,1%). Terdapat hubungan penatalaksaaan Range of motion dengan pencegahan resiko dekubitus pada pasien stroke di RSUD H. Damanhuri Barabai tahun 2023 Kata Kunci: Identifikasi, Pencegahan Risiko Dekubitus, Skala Braden, Range of Motion, Stroke